Hubungan Tingkat Stres, Olahraga, Dan Kepatuhan Minum Obat Dengan Peningkatan Kadar Gula Darah Pada Pasien Diabetes Melitus Tipe 2 Di Poli Penyakit Dalam Rs Siti Aisyah Lubuklinggau Tahun 2025 - Ocviskah Ocviskah; Sasteri Yulianti; Murwati Murwati (Jurnal Multidisiplin Dehasen (MUDE), 2026)
General Hospital in Lubuklinggau City, ranking third in terms of prevalence. The purpose of this study was to determine the relationship between stress levels, exercise, and medication adherence with increased blood glucose levels in patients with type 2 diabetes mellitus at the Internal Medicine Clinic of Siti Aisyah Hospital in Lubuklinggau in 2025.The research method used was a descriptive quantitative approach with a cross-sectional design. The sampling technique employed purposive sampling, with a sample size of 77 participants. The results of the univariate analysis showed that most respondents (51,9%) had moderate stress, most respondents (55.8%) did not exercise properly almost all respondents (39%) had high medication adherence, and many other respondents (62.3%) experienced hyperglycemia. The results of the bivariate analysis showed a relationship between stress levels (0.000), exercise (0.000), and medication adherence (0.000) with increased blood sugar levels in patients with type 2 diabetes mellitus. There is a correlation between stress levels, exercise, and medication adherence with increased blood sugar levels in patients with type 2 diabetes mellitus at the Internal Medicine Clinic of Siti Aisyah Hospital in Lubuklinggau in 2025.The researchers advise the respondents to consistently exercise according to their physical abilities, manage stress with appropriate relaxation techniques, and continue to adhere to medication rules as recommended by health workers.